Law Enforcement on Criminal Acts of Fuel Oil Distribution Illegally Subsided - Achmad Surya; Suhartini Suhartini (UNIFIKASI : Jurnal Ilmu Hukum, 2023)
Misuse of distribution of fuel oil (BBM) often occurs illegally, to gain individual or business entity benefits by harming the interests of the general public and the state. This act is against the law and can be subject to criminal penalties as regulated in Law Number 22 of 2001 concerning Oil and Gas. This type of research is empirical law using primary data obtained directly from the field through interviews with related parties, while secondary data obtained through library data in the form of primary legal materials, namely binding regulations, secondary and tertiary materials. Research results show, law enforcement against the illegal distribution of subsidized fuel oil (BBM) has never been carried out by the Central Aceh Resort Police, due to the absence of reports from the public.Â  The efforts of police investigators in overcoming the crime of distributing subsidized fuel oil (BBM) in Central Aceh Regency. First, Supervise the distribution of subsidized fuel in cooperation with local governments, as well as coordinate with owners of Public Fuel Filling Stations (SPBU). Second, urge the public to report to the police if it is found that the distribution of subsidized fuel is illegal.